The power of the cognitive unconscious: The case of implicit learning - Ziori, Eleni (Psychology: the Journal of the Hellenic Psychological Society, 2023)
The present paper highlights the power of unconscious processes within the framework of implicit learning, a research area that has attracted extensive attention in the past decades. More specifically, it discusses theoretical issues concerning this multifaceted type of learning that occurs without conscious awareness and presents various applications in different learning settings and research domains, and in varied populations. Another main focus of this review is on recent advances in our understanding of the factors that affect implicit learning, including motives, attention, affective states, and general knowledge. The paper ends with conclusions and general principles drawn from research on a phenomenon with extended applications both in the lab and in everyday life and underlines the necessity for further research that will refine our methods of distinguishing conscious and unconscious processes and provide answers to unresolved issues and contradictory findings.